Analisis Determinan Tingkat Proporsi Dana Tabarru’ Pada Asuransi Jiwa Syariah - Nuraini Nuraini; Mustafa Kamal (Jurnal Akuntansi dan Keuangan Islam, 2018)
This research aims to determine influence of the claim risk, retakaful contribution, operating expenses, exchange rate, inflation rate and BI rate toward proportion of tabarru’ funds on Islamic life insurance companies. Sampling is done by purposive sampling technique to get 138 data from different starting ranges data and periods, with the final sample of 23 Islamic life insurance companies during 2010-2017. The method of analysis used in this research is multiple linear regression using unbalanced panel data that processed by using Eviews 9. The result showed that the best estimation model for this research is Random Effect Model (REM). Simultaneously all of the independent variables have significant influence towards proportion of tabarru’ funds. While partially, claim risk has positive significant, retakaful contribution and operating expenses has negative significant influence towards proportion of tabarru’ funds. As for the macroeconomic variables, namely exchange rate, inflation rate and BI rate have no significant influence towards proportion of tabarru’ funds